Probiotics supplementation or probiotic-fortified products on sarcopenic indices in older adults: systematic review and meta-analysis from recent randomized controlled trials - Handajani, Yvonne Suzy; Turana, Yuda; Hengky, Antoninus; Hamid, Gabriella; Schroeder-Butterfill, Elisabeth; Kristian, Kevin (Frontiers in Aging, 2024)
A noteworthy correlation was seen between changes in the gut microbiome and sarcopenia in older adults. Along with increasing research on probiotic supplementation for various medical problems, we aimed to obtain evidence and summarize the effect of probiotic supplementation on sarcopenic indices among older adults.We utilized PubMed, EBSCO, and Proquest, in addition to manual search using synonyms and variation for 'probiotic,' 'sarcopenia,' and 'older adults.' Randomized controlled trials (RCTs) investigated the utilization of probiotics or probiotic-containing products in older adults with sarcopenic indices including muscle mass and strength. The random-effects model was applied to the meta-analysis process.Results: Seven studies were obtained with 733 pooled older adults. Probiotic supplementation resulted in a significant increase of muscle mass with adjusted SMD (Standardized Mean Difference) of 0.962 (95% CI: 0.288 to 1.635, p = 0.049) using till and trim analysis and muscle strength with SMD of 1.037 (95% CI: 0.077 to 1.996, p = 0.03). However, both outcomes were associated with significantly high heterogeneity (I 2 = 89.5% and I 2 = 89.9%, respectively).When opposed to a placebo, the probiotic treatment improved the amount of muscle and its endurance based on recent evidence, however, further studies should be done with larger samples and targeted populations.